Mechanical properties characterization of Ti6Al4V for artificial hip joint materials prepared by investment casting. Issue 1 (January 2022) - Ismail, R; Bayuseno, A P; Fitriyana, D F; Taqriban, R B; Muhamadin, R C; Al Hakim, R A N; Siregar, J P
Abstract: The Investment Casting (IC) process is a type of casting that can produce the suitable shape and size of components by minimizing porosity and defects. However, research on ICs for the manufacture of artificial hip joints made from Ti6Al4V is still lacking. Therefore, the purpose of this study is to determine the mechanical properties of an artificial hip joint made from Ti6Al4V casted using the investment casting method. The stages of the investment casting process used in this research are wax injection, ejection of wax pattern, tree assembly, slurry coating, final sand mould, dewaxing, preheating, pouring, and final product. The characterization of IC products was carried out by tensile test, hardness test, and impact test. The yield strength, Ultimate Tensile Strength, Elongation (%), Hardness (HRC) and Impact Strength obtained in this study were 636 MPa, 687 MPa, 17%, 29 HRC, and 5.3 J, respectively. The lower oxygen content in Ti Alloy after IC resulted in a decrease in yield strength, ultimate tensile strength, hardness, and impact energy. However, the low oxygen content in Ti Alloy after IC resulted in increased ductility (% elongation).